The relationship between market orientation, customer loyalty and business performance: A sample from the Western Europe hotel industry - Sampaio, Carlos (2019)
Submitted by Carlos Sampaio (cfsampaio@ipcb.pt) on 2019-04-07T00:38:24Z No. of bitstreams: 1 The relationship between market orientation, customer loyalty and business performance A sample from the Western Europe hotel industry.pdf: 365185 bytes, checksum: 7f98413dcee5b9da9279d886dfaef704 (MD5)